Seeking Pleasure and Seeking Pain: Differences in Prohedonic and Contra-Hedonic Motivation From Adolescence to Old Age - Michaela Riediger; Florian Schmiedek; Gert G. Wagner; Ulman Lindenberger (Psychological Science, 2009)
Using a mobile-phone-based experience-sampling technology in a sample of 378 individuals ranging from 14 to 86 years of age, we investigated age differences in how people want to influence their feelings in their daily lives. Contra-hedonic motivations of wanting either to maintain or enhance negative affect or to dampen positive affect were most prevalent in adolescence, whereas prohedonic motivations of wanting either to maintain, but not enhance, positive affect or to dampen negative affect were most prevalent in old age. This pattern was mirrored by an age-related increase in self-reported day-to-day emotional well-being. Analyses of the emotional experiences that accompanied prohedonic and contra-hedonic motivations are consistent with the notions that contra-hedonic motivations are more likely to serve utilitarian than hedonic functions, and that people are more likely to be motivated to maintain negative affect when it is accompanied by positive affect. Implications for understanding affective development are discussed.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; Lebensqualität; Zufriedenheit; Lebenszyklus